Shamanization in Central Asia - DeWeese, Devin (Journal of the economic and social history of the Orient, 2014)
A significant body of Muslim religious rites, with roots in Sufi devotional practice, continued to be conducted in Central Asia well into the Soviet era, despite Soviet antireligious policies and pressures. Reflecting communal adaptations of the Sufi dhikr, or “remembrance” of God, as part of healing or funerary ceremonies, these rites were reclassified, in Soviet ethnographic literature, as vestiges of “shamanism,” and thus largely escaped notice by western observers of “Soviet Islam,” who imagined ‘Sufism’ in terms of clandestine militant organizations intent on undermining the Soviet regime. This paper explores the reclassification of Sufi activity as shamanism, notes historical evidence on the diffusion of Sufi rites into wider public circles, and suggests some implications of these developments for our understanding of Soviet Islam, Central Asian Sufism, and the phenomena of “shamanism.”